Neoadjuvant immunotherapy for DNA mismatch repair proficient/microsatellite stable non-metastatic rectal cancer: a systematic review and meta-analysis - Zhang, Huan; Huang, Jing; Xu, Huanji; Yin, Nanhao; Zhou, Liyan; Xue, Jianxin; Ren, Min (Frontiers in Immunology, 2025)
BackgroundNeoadjuvant immunotherapy (NIT) has been endorsed by clinical guidelines for the management of DNA mismatch repair deficiency/microsatellite instability-high (dMMR/MSI-H) locally advanced rectal cancer (LARC). Nonetheless, the therapeutic efficacy of NIT in mismatch repair-proficient/microsatellite stable (pMMR/MSS) non-metastatic rectal cancer (RC) remain pending matters. Therefore, a meta-analysis was carried out to assess the efficacy and safety of NIT in patients with non-metastatic pMMR/MSS RC.MethodsPubMed, Embase, Web of Science, the Cochrane Library, ClinicalTrials.gov, ASCO and ESMO were searched to obtain related studies up to July 2024. Two reviewers independently screened the included articles and extracted the pertinent data. The risk of publication bias was assessed by Begg or Egger tests and in cases of publication bias, the trim and fill method was applied. Heterogeneity was assessed using I 2 statistics.ResultsThirteen articles including 582 eligible patients were analyzed. The pooled pCR, MPR, cCR and anus preservation rate were 37%, 57%, 26% and 77% separately and the incidence of irAEs≥3 grades and TRAEs≥3 grades were 3% and 29%, respectively. Non-metastatic pMMR/MSS RC receiving the short-course radiotherapy (SCRT) in neoadjuvant setting exhibited superior pooled pCR and MPR than long-course radiotherapy (LCRT) without upregulating the incidence of adverse effects. Furthermore, patients with MSS RC underwent neoadjuvant treatment with anti-PD-1 inhibitors demonstrated higher pooled pCR, MPR, cCR compared to those receiving PD-L1 inhibitors. Additionally, yielded improved pooled MPR and anal preservation rates compared to sequential immuno-radiotherapy (63.4% vs 51.2% and 88.5% vs 69.9%), without raising the incidence of irAEs≥3 grade. Interestingly, RC patients with lymph node metastasis showed a higher pooled pCR than those without lymph node metastasis (43% vs 35%).ConclusionNIT was linked to favorable response rates and anal preservation, alongside an acceptable safety profile. Non-metastatic pMMR/MSS RC patients receiving SCRT, PD-1 inhibitors, or concurrent immuno-radiotherapy in the neoadjuvant setting exhibited enhanced outcomes. This meta-analysis provides evidence for further exploration and application of NIT in non-metastatic pMMR/MSS RC and highlights the potential for organ preservation with this approach. The relatively small sample size and the uneven quality of included studies may have had some impact on the generality of the results. Therefore, further analysis with a higher number of high-quality studies is needed to verify the conclusions.Systematic review registrationhttps://inplasy.com/, identifier: INPLASY202470110.